Issues and consequences of newspaper framing on ethnic conflict: a qualitative study of ethnic group leaders’ conflict frames - Adisa, Rasaq Muhammed; Rosli Mohammed,; Mohd. Khairie Ahmad, (Penerbit Universiti Kebangsaan Malaysia, 2016)
This paper attempts to explore the waves of media frames on ethnic group leaders’ conflict frames. In general, the effects of what media frame as news on public behaviours to politics have been discussed extensively in scholarly works. However, the extent that newspapers framing stimulate conflict frame (behaviours) in ethnic leaders who rheostat the hearts and minds of ethnic groups, are still underexplored. Specifically, this study seeks to understand the extent that media frames about ethnic issues have become the driving force behind volatile ethnic groups in Nigeria. Therefore, series of in-depth interviews on 26 ethnic group leaders were conducted and data were analyzed thematically using NVIVO 10 software. The study found that the unswerving newspapers framing on ethnic issues, especially on interethnic relations and politics, culminated to inciting, double standard, name calling, all of which stemmed from the ownership interest, are some of the major factors that widen ethnic differences and eventually stimulated ethnic groups into conflict. Based on the lived experiences of the ethnic group leaders, newspapers are culpable in the emergence and escalation of ethnic conflict as a result of these stimulations. This study has significantly contributed to the understanding of potential influence of conflict frames (behaviors) of ethnic group leaders on ethno-political conflict.